Epidemic and PCR-based identification of vibrio cholera through OmpW gene from diarrheal patients admitted at different hospitals of Baluchistan - Ashiq Hussain; Muhammad Kamran Taj; Muhammad Shafi Khosa; Bezan Baloch; Muhammad Tahir; Abdul Sadiq (Journal of the Pakistan Medical Association, 2021)
Objective: The research was designed to study the different epidemiological and PCR-based identification of Vibrio cholera. Method: The cross sectional study was performed in Center for Advanced Studies in Vaccinology and Biotechnology, University of Balochistan, Quetta from January 5, 2019 till December 6, 2019. Fecal / rectal swab samples were taken with a history of untreated severe (rice water) diarrhea of less than 12 hours duration. Total 444 stool samples were collected from suspected cholera patients at different hospitals of Balochistan. Isolates were examined and identified on the basis of colony characters on TCBS agar. susppected colonies were subjected to gram staining, various biochemical tests and PCR base identification. Results: The result shows that 7.43 % were V.cholerae positive while 92.56% were found negative. The rates of incidence was highest in individuals in 1-20 years old patients as compared to other age group patients. The gender wise distribution of cholera infection was found high in male (4.05%) as compared to female patients (3.37%). The percentage of cholera infection was high in Baluch (4.05%) race as compared to other races of Baluchistan. The status wise distribution showed that lower class (4.05%) was more affected as compared to other classes of Balochistan. Literacy and illiteracy wise distribution showed that the illiterate patients (5.85%) were more affected. The incidence of cholera infection was more in summer (4.27%) and spring (1.80%) seasons as compared to other seasons of Balochistan. Continuous...